Treatment of tumour recurrence after resection of hepatocellular carcinoma. Analysis of 97 consecutive patients - Tralhão, JG (2007)
OBJECTIVE: To evaluate the long-term results of aggressive treatment of HCC recurrence. METHODS: Two hundred and nine consecutive patients underwent hepatic resection for HCC in our hospital. Tumour recurrence was diagnosed in 97 (51%) of the 190 patients with curative resection. Sixteen underwent hepatic resection: two right hepatectomies, one three-segmentectomy, one left hepatectomy, five two-segmentectomies, six segmental resections and one subsegmentectomy. Two patients with metastasis in the spine were submitted to a vertebral body resection. Twenty-five patients were treated with percutaneous ethanol injection or intra-arterial chemoembolization. Fifty-four patients with a poor performance status and liver function or multiple extra hepatic recurrences did not receive any treatment. RESULTS: There were no operative deaths. The postoperative mortality rate was 5.5% (one patient). The cumulative overall survival after the second resection was respectively 89%, 46% and 31% at 1, 3 and 5 years. There was a significant difference in survival between patients treated with repeat resection and those submitted to a non-surgical or conservative treatment (p<0.0001). There were no differences in operative deaths, postoperative mortality and morbidity between the first and second hepatic resection. CONCLUSIONS: Aggressive management with combined resection or loco regional therapy for intrahepatic recurrence and resection of isolated extra-hepatic recurrence may offer long-term survival in selected patients. Second liver resection for recurrence of HCC can be safely performed.